Outcomes of preadolescent children after inpatient psychiatric admission: a scoping review and qualitative study - Swart, Tania (Department of Psychiatry and Mental Health, 2023)
Background: Approximately twenty percent (20%) of children and adolescents have mental health disorders and between 50–75% of all adult mental illness has its onset before the age of 18. Few under 18-year-olds with mental health disorders are, however, admitted for psychiatric inpatient care. The majority of those are adolescents who present with emerging serious mental health disorders. Very little is known about inpatient admission of preadolescent children (under 13 years) with mental health disorders. A review in 2000 showed mixed results about outcomes from admissions and highlighted a number of challenges with outcome studies. Objectives: The purpose of this study was to investigate the outcomes of preadolescents (hereafter referred to as ‘children') after inpatient admission, both locally and internationally. Methods: To meet the first aim, we performed a scoping review. Two reviewers independently searched EBSCOhost and Scopus (January 2000 – February 2017), using keywords ‘inpatient'; ‘psychiatry'; ‘psychiatric unit'; ‘mental health'; ‘children'; ‘treatment outcome/s'; ‘follow-up'; ‘secondary care'; to identify studies examining child (0–12 years) psychiatric inpatient outcomes. To meet the second aim, perspectives of convenience sampled parent-child dyads, who were previously patients at an inpatient psychiatric unit for under 13-year-olds in Cape Town, South Africa, were gathered using in-depth individual interviews. Data generated from the interviews were transcribed and analysed using thematic analysis. Results: Seventeen studies were identified by the PRISMA-guided search strategy in the scoping review. Measurements used differed widely. Significant improvements were reported at discharge and was maintained in short-term follow-up (1–4 months) studies. However, medium-term (5–11 months) and long-term (1 year or more) follow-up studies showed mixed results, with marked deterioration in very long-term studies. The qualitative study showed that most families found inpatient admission helpful, and indicated positive outcomes, but with ongoing difficulties over time. Two main themes related to outcomes emerged from the 10 parent-child dyads included in the study. The first theme (“A turn in the road”) highlighted inpatient admission as the catalyst of positive outcomes. Diagnostic certainty; newly acquired cognitive and behavioural skills; improved parent-child relationships; appropriate school placements; development of peer relationships; as well as follow-up psychiatric care and medication, were seen as contributing to positive outcomes. Conversely, the second theme (“Still a rough journey”) described ongoing difficulties including lingering problems despite improvement; minimal improvement when lacking a diagnosis; regression with transition to mainstream secondary school; and negative outcomes associated with lack of peer relationships and discontinuation of psychiatric care and medication. Conclusion: Taking together findings from our work, inpatient stay for child psychiatric patients was found to result in substantial short-term improvement. Medium-term outcomes were less clear, while long-term outcomes appeared mixed, with potential deterioration in the very long-term. However, the relatively few and diverse studies found in the scoping review made interpretation of the findings difficult. One striking finding from the research, was the absence of internationally agreed outcome measures to inform such research. In this study, qualitative data from families and children who had received inpatient treatment provided several functional outcomes that may be important, both for outcomes research and for post-discharge clinical practice.